Aortic Root Diameter and Longitudinal Blood Pressure Tracking - Ingelsson, Erik (2008)
Proximal aortic diameter, including aortic root (AoR) diameter, has been inversely related to pulse pressure (PP) in cross-sectional studies. So, investigators have hypothesized that a smaller AoR diameter may increase risk of developing hypertension. Prospective studies are lacking to test this hypothesis. We measured AoR diameter in 3195 Framingham Study participants (mean age 49 years, 57% women; 8460 person-examinations) free from hypertension and prior cardiovascular disease who underwent routine echocardiography. We related AoR to hypertension incidence and blood pressure (BP) progression (increment of ≥1 category, as defined by the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure). On follow-up (median 4 years), 1267 individuals (15%, 661 women) developed hypertension and 2978 participants experienced BP progression (35%, 1588 women). In logistic regression models adjusted for age, sex, and height, AoR was positively associated with hypertension incidence (odds ratio [OR], 1.15; 95% confidence interval [CI], 1.08–1.23) and BP progression (OR, 1.09; 95% CI, 1.04–1.14) on follow-up. However, adjustment for other factors known to influence BP tracking (baseline systolic and diastolic blood pressure, smoking, diabetes, and weight) rendered these relations statistically non-significant (OR, 1.03; 95% CI, 0.96–1.11 for hypertension incidence; OR, 1.03; 95% CI, 0.97–1.08 for BP progression). In our large community-based sample of non-hypertensive individuals, AoR diameter was not associated with hypertension incidence or BP progression prospectively after adjustment for potential confounders. Our prospective study does not support the notion that a smaller AoR predisposes to hypertension.